It's All about Me: Narcissistic Chief Executive Officers and Their Effects on Company Strategy and Performance - Chatterjee, Arijit; Hambrick, Donald C. (Administrative Science Quarterly, 2007)
This study uses unobtrusive measures of the narcissism of chief executive officers (CEOs)—the prominence of the CEO's photograph in annual reports, the CEO's prominence in press releases, the CEO's use of first-person singular pronouns in interviews, and compensation relative to the second-highest-paid firm executive—to examine the effect of CEO narcissism on a firm's strategy and performance. Results of an empirical study of 111 CEOs in the computer hardware and software industries in 1992–2004 show that narcissism in CEOs is positively related to strategic dynamism and grandiosity, as well as the number and size of acquisitions, and it engenders extreme and fluctuating organizational performance. The results suggest that narcissistic CEOs favor bold actions that attract attention, resulting in big wins or big losses, but that, in these industries, their firms' performance is generally no better or worse than firms with non-narcissistic CEOs.